2014
DOI: 10.1021/ma500084c
|View full text |Cite
|
Sign up to set email alerts
|

“Inverse Polyampholyte” Hydrogels from Double-Cationic Hydrogels: Synthesis by RAFT Polymerization and Characterization

Abstract: We present two novel, homologous, pyridinebased monomers, 2-(pyridin-2-yl)ethyl methacrylate (PyEMA) and (pyridin-2-yl)methyl methacrylate (PyMMA), which, despite their structural similarity, the former can be readily thermolyzed to methacrylic acid, while the latter remains intact under the same conditions. This was most dramatically demonstrated in the present work, where PyEMA and PyMMA were randomly terpolymerized with a dimethacrylate cross-linker using reversible addition−fragmentation chain transfer pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…This will enable the selective alkaline hydrolysis of the residue from the cleavable linkers, without affecting the ester groups of the monomer repeating units. This selectivity in the alkaline hydrolysis of the 2‐(pyridin‐2‐yl)ethanol mono‐ and di‐esters relative to common methacrylate monomers has already been demonstrated in our previous studies on polymers bearing PyEMA monomer repeating units and PyDMA cross‐linker units…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This will enable the selective alkaline hydrolysis of the residue from the cleavable linkers, without affecting the ester groups of the monomer repeating units. This selectivity in the alkaline hydrolysis of the 2‐(pyridin‐2‐yl)ethanol mono‐ and di‐esters relative to common methacrylate monomers has already been demonstrated in our previous studies on polymers bearing PyEMA monomer repeating units and PyDMA cross‐linker units…”
Section: Resultssupporting
confidence: 74%
“…We recently imported this to polymer chemistry, to protect methacrylic acid (MAA), transforming it to 2‐(pyridin‐2‐yl)ethyl methacrylate (PyEMA), polymerizing it, and then readily removing the protecting group in the form of 2‐vinylpyridine, either by treatment with sodium hydroxide solution at RT or by thermolysis in the temperature range between 110 °C and 160 °C under neutral conditions in the bulk or in solution . Furthermore, we showed that the PyEMA units in terpolymers with 2‐tetrahydropyranyl methacrylate (THPMA) and benzyl methacrylate (BzMA) are preserved under acidic hydrolysis conditions where the THPMA units are readily converted to MAA units . Additionally, we demonstrated that the polymer of the lower homologous group, the (pyridin‐2‐yl)methyl group, formed a much more stable MAA ester, (pyridin‐2‐yl)methyl methacrylate (PyMMA) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels may be synthesized via several different ways such as thermal- [25], redox- [26], RAFT- [27,28] and photopolymerization [29]. This last method that corresponds to a photoinitiated radical polymerization of multifunctional monomers that produce highly crosslinked polymers, has several advantages over conventional ones like spatial and temporal control, fast curing and reaction rates at room temperature, solvent-free formulation, among others.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, poly(oligoethylene glycol (meth)acrylate)s, [3][4][5][6][7] poly(2-oxazoline)s, [8][9][10][11][12][13] poly(vinyl ether)s 14 and polypeptides 15,16 have also been widely studied and have found various applications as smart materials. 38 The development of polyampholytes based on cationic and anionic monomers with UCST behavior is extremely challenging as both monomers need to be incorporated in stoichiometric amounts. Compared with polymers that undergo an LCST transition, such polymers exhibiting UCST behavior in aqueous solution have been much less documented as it is much more challenging to achieve this behavior in aqueous solutions requiring strong interpolymer attraction in combination with high hydrophilicity.…”
mentioning
confidence: 99%